Cut age and N balance in pigs fed with Moringa oleifera foliage meal - Mireles, S.; Moreno, E.; Samkol, Pok; Caro, Y.; Ly, J. (Cuban Journal of Agricultural Science, 2017)
In order to study the influence of the cut age, every 60 or 120 days, of Moringa (Moringa oleifera) foliage on the N balance of pigs fed diets with 15% meal of this foliage, a change over design with six YxL pigs, castrated males was applied. These animals averaged approximately 15 kg of live weight. The moringa, with 60 or120 d of cut, contained 11.0 or 23.3 % of crude fiber, and 23.3 or 19.8 % of crude protein, respectively. These cut ages were also evaluated by in vitro digestibility (pepsin / pancreatin and fecal). The rectal digestibility, such as the N retention, were significantly higher (P <0.05) in the individuals fed with foliage cut every 60 d (75.9 and 40.6%) with respect to the obtained at 120 d of cut (70.0 and29.3%). The experiment showed that the moringa foliage aging determines the decrease of the digestive exploitation and the N balance in pigs fed with diets containing this foliage.Key words: pigs, digestibility, nutritional value, protein, Moringaoleifera